Razlogi študentov za izbiro poklica učitelj razrednega pouka - Ivanuš-Grmek, Milena; Lačen, Iztok (Revija za elementarno izobraževanje, 2008)
Reasons why University Students Choose the Teaching Profession. The article describes the results of research done about the reasons why students choose the teaching profession. 128 university students participated in the research. The students were comprised of freshmen and seniors enrolled in the Elementary Education program at the Faculty of Education. In the research we were interested in the reasons why students choose teaching as a profession, the degree of satisfaction with their choice and the working conditions at the faculty. Of the five groups we researched, most students chose the teaching profession for altruistic and self-realization reasons. Very few of the students chose the profession because of materialistic and alternative reasons. There were no statistically significant differences found among freshmen and senior students regarding their reasons for choosing the teaching profession. The study also shows that the students are mainly satisfied with their choice of study and that their satisfaction and expectations regarding their study program decrease with years of study
Keywords: education; elementary school; teachers; choice of profession; motivation